Tools and approaches for analysing the role of mitochondria in health, development and disease using human cerebral organoids - Liput, Michał; Magliaro, Chiara; Kuczyńska, Zuzanna; Zayat, Valery; Ahluwalia, Arti; Buzanska, Leonora (Developmental Neurobiology, 2021)
Mitochondria are cellular organelles involved in generating energy to power various processes in the cell. Although the pivotal role of mitochondria in neurogenesis was demonstrated (first in animal models), very little is known about their role in human embryonic neurodevelopment and its pathology. In this respect human-induced pluripotent stem cells (hiPSC)-derived cerebral organoids provide a tractable, alternative model system of the early neural development and disease that is responsive to pharmacological and genetic manipulations, not possible to apply in humans. Although the involvement of mitochondria in the pathogenesis and progression of neurodegenerative diseases and brain dysfunction has been demonstrated, the precise role they play in cell life and death remains unknown, compromising the development of new mitochondria-targeted approaches to treat human diseases. The cerebral organoid model of neurogenesis and disease in vitro provides an unprecedented opportunity to answer some of the most fundamental questions about mitochondrial function in early human neurodevelopment and neural pathology. Largely an unexplored territory due to the lack of tools and approaches, this review focuses on recent technological advancements in fluorescent and molecular tools, imaging systems, and computational approaches for quantitative and qualitative analyses of mitochondrial structure and function in three-dimensional cellular assemblies-cerebral organoids. Future developments in this direction will further facilitate our understanding of the important role or mitochondrial dynamics and energy requirements during early embryonic development. This in turn will provide a further understanding of how dysfunctional mitochondria contribute to disease processes.
Keywords: cerebral organoids; computational models; mitochondria imaging; mitochondrial dyes; reporter fluorescent proteins.

Compliance Control of a Cable-Suspended Aerial Manipulator using Hierarchical Control Framework - C. Gabellieri; Y. S. Sarkisov; A. Coelho; L. Pallottino; K. Kondak; M. J. Kim (2020 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2020)

Comparison of Three Hand Pose Reconstruction Algorithms Using Inertial and Magnetic Measurement Units - P. J. Kieliba; P. H. Veltink; T. Lisini Baldi; D. Pratichizzo; G. Santaera; A. Bicchi; M. Bianchi; B. J. F. Van Beijnum (18th IEEE-RAS International Conference on Humanoid Robots, Humanoids 2018, 2019)

Design and Validation of a Modular One-To-Many Actuator for a Soft Wearable Exosuit - M. Xiloyannis; E. Annese; M. Canesi; A. Kodian; A. Bicchi; S. Micera; A. Ajoudani; L. Masia (Frontiers in Neurorobotics, 2019)

Dynamic motion control of multi-segment soft robots using piecewise constant curvature matched with an augmented rigid body model - R. K. Katzschmann; C. D. Santina; Y. Toshimitsu; A. Bicchi; D. Rus (RoboSoft 2019 - 2019 IEEE International Conference on Soft Robotics, 2019)

An Objective Functional Evaluation of Myoelectrically-Controlled Hand Prostheses: A Pilot Study Using the Virtual Peg Insertion Test - C. M. Kanzler; M. G. Catalano; C. Piazza; A. Bicchi; R. Gassert; O. Lambercy (IEEE International Conference on Rehabilitation Robotics (ICORR), 2019)

Dynamic Control of Soft Robots Interacting with the Environment - C. Della Santina; R. K. Katzschmann; A. Bicchi; D. Rus (IEEE International Conference on Soft Robotics, 2018)
Keywords: Robotics

Humanoids at Work: The WALK-MAN Robot in a Postearthquake Scenario - F. Negrello; A Settimi; D. Caporale; G. Lentini; M. Poggiani; D. Kanoulas; L. Muratore; Luberto, E.; G. Santaera; L. Ciarleglio; L. Ermini; L. Pallottino; et al. (IEEE Robotics Automation Magazine, 2018)
Keywords: Buildings; Earthquakes; Hardware; Legged locomotion; Robot sensing systems; Task analysis

WALK-MAN Humanoid Platform - N. G. Tsagarakis; F. Negrello; M. Garabini; W. Choi; L. Baccelliere; V. G. Loc; J. Noorden; M. G. Catalano; M. Ferrati; L. Muratore; P. Kryczka; E. Mingo Hoffman; et al. (The DARPA Robotics Challenge Finals: Humanoid Robots To The Rescue, 2018)

WALK-MAN: A High-Performance Humanoid Platform for Realistic Environments - N. G. Tsagarakis; D. G. Caldwell; F. Negrello; W. Choi; L. Baccelliere; V. G. Loc; J. Noorden; L. Muratore; A. Margan; A. Cardellino; L. Natale; E. Mingo Hoffman; et al. (Journal of Field Robotics, 2017)
In this work, we present WALK-MAN, a humanoid platform that has been developed to operate in realistic unstructured environment, and demonstrate new skills including powerful manipulation, robust balanced locomotion, high-strength capabilities, and physical sturdiness. To enable these capabilities, WALK-MAN design and actuation are based on the most recent advancements of series elastic actuator drives with unique performance features that differentiate the robot from previous state-of-the-art compliant actuated robots. Physical interaction performance is benefited by both active and passive adaptation, thanks to WALK-MAN actuation that combines customized high-performance modules with tuned torque/velocity curves and transmission elasticity for high-speed adaptation response and motion reactions to disturbances. WALK-MAN design also includes innovative design optimization features that consider the selection of kinematic structure and the placement of the actuators with the body structure to maximize the robot performance. Physical robustness is ensured with the integration of elastic transmission, proprioceptive sensing, and control. The WALK-MAN hardware was designed and built in 11 months, and the prototype of the robot was ready four months before DARPA Robotics Challenge (DRC) Finals. The motion generation of WALK-MAN is based on the unified motion-generation framework of whole-body locomotion and manipulation (termed loco-manipulation). WALK-MAN is able to execute simple loco-manipulation behaviors synthesized by combining different primitives defining the behavior of the center of gravity, the motion of the hands, legs, and head, the body attitude and posture, and the constrained body parts such as joint limits and contacts. The motion-generation framework including the specific motion modules and software architecture is discussed in detail. A rich perception system allows the robot to perceive and generate 3D representations of the environment as well as detect contacts and sense physical interaction force and moments. The operator station that pilots use to control the robot provides a rich pilot interface with different control modes and a number of teleoperated or semiautonomous command features. The capability of the robot and the performance of the individual motion control and perception modules were validated during the DRC in which the robot was able to demonstrate exceptional physical resilience and execute some of the tasks during the competition.
Keywords: Robotics

A Full Body Sensing System for Monitoring Stroke Patients in a Home Environment - Klaassen, B.; van Beijnum, B.J.F.; Weusthof, M. H. H.; D. Hofs; van Meulen, F.B.; E. Droog; H. Luinge; S. Laurens; A. Tognetti; F. Lorussi; R. Paradiso; Held, J.; et al. (Biomedical Engineering Systems and Technologies: 7th International Joint Conference, BIOSTEC 2014, Angers, France, March 3-6, 2014, Revised Selected Papers, 2016)
Keywords: Bioengineering

Hand synergies: Integration of robotics and neuroscience for understanding the control of biological and artificial hands - M. Santello; M. Bianchi; M Gabiccini; E. Ricciardi; G. Salvietti; D Prattichizzo; M. Ernst; A. Moscatelli; H. Jorntell; A. Kappers; K. Kyriakopulos; A Albu-Schaeffer; et al. (Physics of Life Reviews, 2016)
Keywords: Haptics; Robotics

A Hands-Free Interface for Controlling Virtual Electric-Powered Wheelchairs - Gulrez, T; A. Tognetti; W. J. YooN; Kavakli-Thorne, M.; J.-J. Cabibihan (INTERNATIONAL JOURNAL OF ADVANCED ROBOTIC SYSTEMS, 2016)
Keywords: Assistive Technologies; Electric-powered Wheelchair; Hands-free Interface

Motion Primitive Based Random Planning for Loco–Manipulation Tasks - A Settimi; D. Caporale; P. Kryczka; M. Ferrati; L. Pallottino (IEEE International Conference on Humanoid Robots (HUMANOIDS 2016), 2016)
Several advanced control laws are available for complex robotic systems such as humanoid robots and mobile manipulators. Controls are usually developed for locomotion or for manipulation purposes. Resulting motions are usually executed sequentially and the potentiality of the robotic platform is not fully exploited. In this work we consider the problem of loco–manipulation planning for a robot with given parametrized control laws known as primitives. Such primitives, may have not been designed to be executed simultaneously and by composing them instability may easily arise. With the proposed approach, primitives combination that guarantee stability of the system are obtained resulting in complex whole–body behavior. A formal definition of motion primitives is provided and a random sampling approach on a manifold with limited dimension is investigated. Probabilistic completeness and asymptotic optimality are also proved. The proposed approach is tested both on a mobile manipulator and on the humanoid robot Walk-Man, performing loco–manipulation tasks.
This work is supported by the European commission project Walk-Man EU FP7-ICT no. 611832 and the ECs Horizon 2020 robotics program ICT-23-2014 under grant agreement 644727 (CogIMon)
Keywords: Robotics

No More Heavy Lifting: Robotic Solutions to the Container Unloading Problem - T. Stoyanov; N. Vaskeviciusz; C. A. Mueller; T. Fromm; R. Krug; V. Tincani; R. Mojtahedzadeh; S. Kunaschk; R. M. Ernits; D. R. Canelhas; M. Bonilla; S. Schwertfeger; et al. (IEEE Robotics and Automation Magazine, 2016)
Keywords: Robotics

Predicting Mood Changes in Bipolar Disorder through Heartbeat Nonlinear Dynamics - G. Valenza; M. Nardelli; C. Gentili; G. Bertschy; M. Kosel; E. P. Scilingo (IEEE Journal of Biomedical and Health Informatics, 2016)
Keywords: Bioengineering

WALK-MAN humanoid lower body design optimization for enhanced physical performance - F. Negrello; M. Garabini; M. G. Catalano; P. Kryczka; W. Choi; D. G. Caldwell; A. Bicchi; N. G. Tsagarakis (IEEE International Conference of Robotics and Automation (ICRA2016), 2016)
The deployment of robots to assist in environments hostile for humans during emergency scenarios require robots to demonstrate enhanced physical performance, that includes adequate power, adaptability and robustness to physical interactions and efficient operation. This work presents the design and development of the lower body of the new high performance humanoid WALK-MAN, a robot developed recently to assist in disaster response scenarios. The paper introduces the details of the WALK-MAN lower-body, highlighting the innovative design optimization features considered to maximize the leg performance. Starting from the general lower body specifications the objectives of the design and how they were addressed are introduced, including the selection of the leg kinematics, the arrangement of the actuators and their integration with the leg structure to maximize the range of motion, reduce the leg mass and inertia, and shape the leg mass distribution for better dynamic performance. Physical robustness is ensured with the integration of elastic transmission and impact energy absorbing covers. Experimental walking trials demonstrate the correct operation of the legs while executing a walking gait.
Keywords: Robotics

Open Biomedical Engineering Education in Africa - A. Ahluwalia; D. Atwine; C. De Maria; C. Ibingira; E. Kipkorir; F. Kiros; J. Madete; D. Mazzei; E. Molyneux; K. Moonga; M. Moshi; M. Nzomo; et al. (The 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBS), 2015)
Keywords: Bioengineering

Tele- Impedance based Assistive Control for a Compliant Knee Exoskeleton: Stiffness Augmentation and Motion Assistance - N. Karavas; A. Ajoudani; N G Tsagarakis; J. Saglia; A. Bicchi; D. Caldwell (Robotics and Autonomous Systems, 2015)
<div class="abstract svAbstract " data-etype="ab" style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; color: rgb(46, 46, 46); line-height: 23.68px;"> This paper presents a tele-impedance based assistive control scheme for a knee exoskeleton device. The proposed controller captures the user’s intent to generate task-related assistive torques by means of the exoskeleton in different phases of the subject’s normal activity. To do so, a detailed musculoskeletal model of the human knee is developed and experimentally calibrated to best match the user’s kinematic and dynamic behavior. Three dominant antagonistic muscle pairs are used in our model, in which electromyography (EMG) signals are acquired, processed and used for the estimation of the knee joint torque, trajectory and the stiffness trend, in real time. The estimated stiffness trend is then scaled and mapped to a task-related stiffness interval to agree with the desired degree of assistance. The desired stiffness and equilibrium trajectories are then tracked by the exoskeleton’s impedance controller. As a consequence, while minimum muscular activity corresponds to low stiffness, i.e. highly transparent motion, higher co-contractions result in a stiffer joint and a greater level of assistance. To evaluate the robustness of the proposed technique, a study of the dynamics of the human–exoskeleton system is conducted, while the stability in the steady state and transient condition is investigated. In addition, experimental results of standing-up and sitting-down tasks are demonstrated to further investigate the capabilities of the controller. The results indicate that the compliant knee exoskeleton, incorporating the proposed tele-impedance controller, can effectively generate assistive actions that are volitionally and intuitively controlled by the user’s muscle activity.
special issue "Wearable Robotics"
Keywords: Robotics

Biomechanisch sichere Geschwindigkeitsregelung fur die Mensch-Roboter Interaktion - S. Haddadin; S. Haddadin; A. Khoury; T. Rokahr; S. Parusel; R. Burgkart; A. Bicchi; A Albu-Schaeffer (At-Automatisierungstechnik, 2014)
Keywords: Robotics

Daily-life tele-monitoring of motor performance in stroke survivors - Veltink, P.H.; van Meulen, F.B.; van Beijnum, B.J.F.; Klaassen, B.; Hermens, H. J.; Droog, E.; Weusthof, M. H. H.; F. Lorussi; A. Tognetti; Reenalda, J.; Nikamp, C. D. M.; Baten, C. T. M.; et al. (Proceedings of XIII International Symposium on 3D Analysis of Human Movement, 2014)
The objective of the EU project INTERACTION is to develop an unobtrusive and modular sensing system for objective monitoring of daily-life motor performance of stroke survivors. This will enable clinical professionals to advise their patients about their continued daily-life activity profile and home training, and evaluate and optimize rehabilitation programs.A modular textile-integrated sensing system was developed and performance and capacity measures were proposed and clinically tested in stroke subject.Telemonitoring facilities were developed and tested. In the last stage of the project, the system will be tested during daily-life.

Decoding 2D kinematics of human arm for body machine interfaces - Gulrez, T; Kavakli-Thorne, M.; A. Tognetti (Proceedings of the 2013 IEEE 8th Conference on Industrial Electronics and Applications, ICIEA 2013, 2014)

Drum Stroke Variation Using Variable Stiffness Actuators - Y. Kim; M. Garabini; J. Park; A. Bicchi (IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2014), 2014)
One interesting field of robotics technology is related to the entertainment industry. Performing a musical piece using a robot is a difficult task because music presents many features like melody, rhythm, tone, harmony and so on. Addressing these tasks with a robot is not trivial to implement. Most of approaches which related to this specific field lacks of quality to perform in front of human audience. Implementation of human-like motions can not be properly achieved with a conventional robot actuator. Consequently, we exploit a new type of actuator which simplifies the drawbacks of a conventional one. We used Variable Stiffness Actuator(VSA) instead of using conventional actuator. We can control position, force, and stiffness, simultaneously by using VSA. The most important novel feature is its controllable stiffness. When the stiffness of the actuator is changed, the characteristics of the actuator's response also changes. We implemented the specific stroke which is called “double stroke” using one of variable stiffness actuator. Although the double stroke is known as a special stroke which could be performed by human only, double stroke is successfully implemented by stiffness variation.
Keywords: Robotics

Haptic Exploration of Unknown Surfaces with Discontinuities - Jamisola, R. S.; Kormushev, P.; A. Bicchi; D. G. Caldwell (Proc. IEEE/RSJ Intl Conf. on Intelligent Robots and Systems (IROS 2014), 2014)
Keywords: Haptics; Robotics

Peripheral Machine Interfaces: going beyond traditional surface electromyography - C. Castellini; P. Artemiadis; M. Wininger; A. Ajoudani; M. Alimusaj; A. Bicchi; B. Caputo; W. Craelius; S. Dosen; K. Englehart; D. Farina; A. Gijsberts; et al. (Frontiers in Neurorobotics, 2014)
Keywords: Robotics

Velvet Fingers: Grasp Planning and Execution for an Underactuated Gripper with Active Surfaces - R. Krug; T. Stoyanov; M. Bonilla; V. Tincani; N. Vaskeviciusz; G Fantoni; A. Birkz; A. Lilienthal; A. Bicchi (2014 IEEE International Conference on Robotics and Automation, 2014)
In this work we tackle the problem of planning grasps for an underactuated gripper which enable it to retrieve target objects from a cluttered environment. Furthermore, we investigate how additional manipulation capabilities of the gripping device, provided by active surfaces on the inside of the fingers, can lead to performance improvement in the grasp execution process. To this end, we employ a simple strategy, in which the target object is `pulled-in' towards the palm during grasping which results in firm enveloping grasps. We show the effectiveness of the suggested methods by means of experiments conducted in a real-world scenario.
Keywords: Haptics; Robotics

Neural correlates of haptic pop-out of shape discrimination in the human brain - A. Leo; M. Feurra; S. Rossi; A. Kappers; A. Bicchi; D Prattichizzo; Cristea, I.; David, D.; P. Pietrini; E. Ricciardi (19th Annual Meeting of the Organization for Human Brain Mapping, 2013)

Optimal Control for Maximizing Velocity of the CompActTM Compliant Actuator - L. Chen; M. Garabini; M. Laffranchi; N. Kashiri; N G Tsagarakis; A. Bicchi; D. G. Caldwell (IEEE International Conference on Robotics and Automation (ICRA2013), 2013)
Keywords: Robotics

Tele-Impedance based Stiffness and Motion Augmentation for a Knee Exoskeleton Device - N. Karavas; A. Ajoudani; N G Tsagarakis; J. Saglia; A. Bicchi; D. G. Caldwell (IEEE International Conference on Robotics and Automation (ICRA2013), 2013)
Keywords: Robotics

On Making Robots Understand Safety: Embedding Injury Knowledge into Control - S. Haddadin; S. Haddadin; A. Khoury; T. Rokahr; S. Parusel; R. Burgkart; A. Bicchi; A Albu-Schaeffer (International Journal of Robotics Research, 2012)
Keywords: Robotics

A truly safely moving robot has to know what injury it may cause - S. Haddadin; S. Haddadin; A. Khoury; T. Rokahr; S. Parusel; R. Burgkart; A. Bicchi; A Albu-Schaeffer (International Conference of Intelligent Robots and Systems - IROS 2012, 2012)
Keywords: Robotics

Visual appearance mapping for optimal vision based servoing - D. Fontanelli; P Salaris; F. A. W. Belo; A. Bicchi (Springer, 2009)
Keywords: Robotics

Comparative study of porous and engineered biomaterials - Mattioli-Belmonte, M.; K KYRIAKIDOU; LUCARINI, G; ZIZZI, A; A. Ahluwalia; G. Vozzi (INTERNAL MEDICINE, 2008)
Keywords: Bioengineering

Optimization of PAM Scaffolds for Neural Tissue Engineering: Preliminary Study on an SH-SY5Y Cell Line - KULLENBERG, J; ROSATINI, F; G. Vozzi; BIANCHI, F; A. Ahluwalia; C. Domenici (TISSUE ENGINEERING, PART A, 2008)
Keywords: Bioengineering

PAM Composite Scaffold of PCL and Carbon NanoTubes for Bone Tissue Regeneration - Mattioli-Belmonte, M.; Fantauzzi, V; K KYRIAKIDOU; Tirella, A; A. Ahluwalia; G. Vozzi (National Conference of Bioengineering, 2008)
poster
Keywords: Bioengineering

Rapid-prototyped and salt-leached PLGA scaffolds condition cell morpho-functional behaviour - Mattioli-Belmonte, M.; G. Vozzi; K KYRIAKIDOU; PULIERI, E; LUCARINI, G; Vinci, B.; PUGNALONI, A; BIAGINI, G; A. Ahluwalia (JOURNAL OF BIOMEDICAL MATERIALS RESEARCH. PART A, 2008)
Keywords: Bioengineering

Symbolic Planning and Control of Robot Motion: Finding the Missing Pieces of Current Methods and Ideas - C. Belta; A. Bicchi; M. Egerstedt; E. Frazzoli; E. Klavins; G. J. Pappas (Robotics and Automation Magazine, 2007)
Approaches to robot motion planning and control that involve tools such as automata, languages, temporal logics, and grammars, have been recently termed "symbolic." In this article, we review some existing results, discuss their relevance and applicability, and outline some of the main open questions and challenges in the area.
Keywords: Embedded Control; Robotics

Adaptive output feedback control of spacecraft relative translation - R. Kristiansen; A. Lor; A. Chaillet; P. J. Nicklasson (Proc. IEEE Int. Conf. on Decision and Control, 2006)
We address the problem of tracking relative translation in a leader-follower spacecraft formation using feedback from relative position only and under parameter uncertainty (spacecraft mass) and uncertainty in the leader variables (true anomaly rate and rate of change). We only assume boundedness of orbital perturbations and the leader control force but with unknown bounds. Under these conditions we propose a controller that renders the closed-loop system, uniformly semiglobally practically asymptotically stable. In particular, the domain of attraction can be made arbitrarily large by picking convenient gains, and the state errors in the closed-loop system are proved to converge from any initial condition within the domain of attraction to a ball in close vicinity of the origin in a stable way; moreover, this ball can be diminished arbitrarily by increasing the gains in the control law. Simulation results of a leader-follower spacecraft formation using the proposed controller are presented.
Keywords: Robotics

Output feedback control of relative translation in a leader-follower spacecraft formation - R. Kristiansen; A. Lor; A. Chaillet; P. J. Nicklasson (Springer Verlag, 2006)
We present a solution to the problem of tracking relative translation in a leader-follower spacecraft formation using feedback from relative position only. Three controller configurations are presented which enables the follower spacecraft to track a desired reference trajectory relative to the leader. The controller design is performed for different levels of knowledge about the leader spacecraft and its orbit. The first controller assumes perfect knowledge of the leader and its orbital parameters, and renders the equilibrium points of the closed-loop system uniformly globally asymptotically stable (UGAS). The second controller uses the framework of the first to render the closed-loop system uniformly globally practically asymptotically stable (UGPAS), with knowledge of bounds on some orbital parameters, only. That is, the state errors in the closed-loop system are proved to converge from any initial conditions to a ball in close vicinity of the origin in a stable way, and this ball can be diminished arbitrarily by increasing the gains in the control law. The third controller, based on the design of the second, utilizes adaptation to estimate the bounds that were previously assumed to be known. The resulting closed-loop system is proved to be uniformly semiglobally practically asymptotically stable (USPAS). The last two controllers assume boundedness only of orbital perturbations and the leader control force. Simulation results of a leader-follower spacecraft formation using the proposed controllers are presented.
Keywords: Robotics

Robustness of PID controlled manipulators with respect to external disturbances - A. Chaillet; A. Lor; R. Kelly (Proc. IEEE Int. Conf. on Decision and Control, 2006)
We present a robustness analysis for PID-controlled robot manipulators. For robot manipulators under the influence of external disturbances we provide a proof, and a tuning procedure, to establish uniform semiglobal practical asymptotic stability. In particular, in contrasts to other works on robust stability of PIDs, we do not use La Salle's principle but provide a strict Lyapunov function. The perturbations that we consider include discontinuous functions of the state, such as Coulomb friction. As corollaries of our main results, one may conclude the same stability property for the case of motion control using linear PID.
Keywords: Robotics

A virtual vehicle approach to underway replenishment - E. Kyrkjebo; E. Panteley; A. Chaillet; K. Pettersen (Springer Verlag, 2006)
The problem of coordinated control of a leader-follower system is solved using a virtual vehicle approach to alleviate information requirements on the leader. The virtual vehicle stabilizes to a shifted reference position/heading defined by the leader, and provides a reference velocity for the synchronization control law of the follower. Only position/heading measurements are available from the leader, and the closed-loop errors are shown to be uniformly globally practically asymptotically stable.
Keywords: Robotics

Variable Stiffness Actuators for Fast and Safe Motion Control - A. Bicchi; G. Tonietti; M. Bavaro; M. Piccigallo (Proceedings of the International Symposium on Robotics Research, 2003)
In this paper we propose Variable Stiffness actuation as a viable mechanical/control co-design approach for guaranteeing control performance for robot arms that are inherently safe to humans in their environment. A new actuator under development in our Lab is then proposed, which incorporate the possibility to vary transmission stiffness during motion execution, thus allowing substantial motion speed-up while maintaining low injury risk levels.
Keywords: Robotics

Robotic Grasping and Manipulation - A. Bicchi; V. Kumar (Ramsete: Articulated and mobile robots for services and Technology, 2001)
Keywords: Grasping; Haptics; Robot Hands

Robotic Grasping and Contact: A Review - A. Bicchi; V. Kumar (Proc. IEEE Int. Conf. on Robotics and Automation, 2000)
Keywords: Grasping; Haptics; Robot Hands

Contact and Grasp Robustness Measures: Analysis and Experiments - D Prattichizzo; J. K. Salisbury; A. Bicchi (Experimental Robotics-IV, 1996)
In this paper we discuss some aspects related to the practical assessment of the quality of a grasp by a robotic device on objects of unknown shape, based on sensorial feedback from tactile and force sensors on the hand. We briefly discuss the concept of contact robustness and of grasp robustness, pointing out that the former is an easily computable but overconservative sufficient condition for the latter. Some experimental results on a simple gripper, the so–called ``Instrumented Talon'', are reported as an illustration.
Keywords: Grasping; Haptics; Robot Hands

Geoacoustic seafloor exploration with a towed array in a shallow water area of the Strait of Sicily - A. Caiti; S. M. Jesus; A. Kristensen (IEEE JOURNAL OF OCEANIC ENGINEERING, 1996)

BEAMFORMING ON SEISMIC INTERFACE WAVES WITH AN ARRAY OF GEOPHONES ON THE SHALLOW SEA-FLOOR - J. A. Tencate; T. G. Muir; A. Caiti; A. Kristensen; J. F. Manning; J. A. Shooter; R. A. Koch; E. Michelozzi (IEEE JOURNAL OF OCEANIC ENGINEERING, 1995)

Quasi-Static Compensation of Force Errors for Flexible Manipulators - A. Bicchi; C. Melchiorri (Selected papers from the Third IFAC/IFIS/IMAC Symposium on Robot Control, 1992)
Keywords: Robotics